Effect of foliar nutrition on productivity and profitability of mungbean (Vigna radiata) in western Rajasthan - MOTI LAL MEHRIYA; BHERU LAL KUMHAR; DEVENDRA SINGH; SURENDRA KUMAR; ANIL KUMAR VERMA; SARITA (The Indian Journal of Agricultural Sciences)
The experiment was conducted during rainy (kharif) seasons of 2021 and 2022 at Agricultural Research Station (Agriculture University, Jodhpur, Rajasthan), Mandor, Rajasthan to evaluate the impact of foliar nutrient application on mungbean [Vigna radiata (L.) Wilczek] growth, yield, and economic returns. The mungbean variety GM4 was used for the study. The treatment was laid out in a randomized block design (RBD) comprised of 8 treatments, viz. T1, Water spray; T2, 2% urea; T3, 2% DAP (diammonium phosphate); T4, NPK (18:18:18) @2%; T5, 0.5% ZnSO4; T6, 2% urea + 0.5% ZnSO4; T7, 2% DAP + 0.5% ZnSO4; and T8, NPK (18:18:18) @2% + 0.5% ZnSO4, replicated thrice. All foliar nutrient applications were performed at pre-flowering and pod initiation stages. The treatment involving foliar spray of NPK (18:18:18) @2% + 0.5% ZnSO4 during these stages exhibited superior performance in terms of growth parameters and yield, including number of nodules/plant, plant height (cm), number of branches/plant, number of pods/plant, number of seeds/pod, test weight (g), and overall yield compared to the control. This treatment showed comparable efficacy to the application of 2% NPK (18:18:18). Additionally, foliar application of NPK (18:18:18) @2% + 0.5% ZnSO4 resulted in significantly higher gross monetary returns (₹107,096/ha) and net monetary returns (₹80,156/ha). However, the treatment combining 2% urea + 0.5% ZnSO4 exhibited the highest benefit to cost ratio.